Characterization of Metacarpal Fractures in a Military Population. Issue 8 (1st August 2016) - Dichiera, Robert; Dunn, John; Bader, Julia; Bulken-Hoover, Jamie; Pallis, Mark
ABSTRACT: The purpose of this study was to investigate the incidence and type of metacarpal (MC) fractures in a military population, and whether these fractures are related to age, military occupational specialty, aggression, or accidental injury. A retrospective record-based review was conducted at a single military center over a 5-year period. Service members with index finger through small finger MC fracture were identified. Data were collected utilizing Armed Forces Health Longitudinal Technology Application and electronic profile (e-profile) databases. Data collected included demographic information, mechanism of injury, nature of injury, total number of visits, and estimated time on physical restriction. 400 patients met inclusion criteria. Males accounted for 94% of the study population, 75% of fractures were of the small finger MC, 54% of patients were between 20 and 24 years, 90% were sustained by junior enlisted personnel, and most occurred by punching. Men aged <25 years were more likely to have intentional injuries. Total time on limited duty profile averaged 38 days and the average medically nondeployable profile was 26 days. MC fractures most commonly affect young, male, junior enlisted service members and are often self-inflicted. As a result, these injuries account for time lost at work, reduced job performance, and decreased medical readiness.